Analisis Perencanaan Anggaran Operasional Mebel X - Adinda Hesti Wulandari; Purwati Purwati; Neneng Miskiyah (Jurnal Bisnis Kreatif dan Inovatif, 2025)
The purpose of this study was to gain a better understanding of how the operational budget planning process is applied to the Mebel Serba Usaha (Mebel Serba Usaha) business, which falls into the micro, small, and medium-sized business category. A quantitative descriptive approach was used, collecting data through direct interviews and observing business activities. The obtained data was then examined to determine costs. Furthermore, sales records over the past four years were evaluated for their use. The analysis revealed that Mebel Serba Usaha has never created an operational budget. This situation makes it difficult for the company to manage its finances, which ultimately impacts performance and profitability. The study shows that an operational budget is a crucial tool for more targeted financial management. Operational budget planning helps companies develop long-term business plans and organize and monitor expenses. The results of this study also emphasize that the absence of a budget tends to make companies lack a clear reference point for determining sales targets and controlling production costs. With structured budget planning, companies can more easily identify spending priorities, estimate cash flow, and assess the efficiency of resource use. Furthermore, implementing an operational budget can improve managerial discipline because every financial decision is based on careful planning, not just on immediate needs. Another benefit is increased transparency in fund management, thereby minimizing the risk of waste or misallocation of costs. Therefore, this study provides a practical contribution in the form of recommendations on the importance of implementing an operational budget for micro, small, and medium enterprises, particularly in maintaining sustainability and increasing competitiveness amidst increasingly fierce business competition.This research is expected to be a reference for other MSMEs in developing a more effective and sustainable financial system.